The causes of poverty - Layard, P. R. G.; Piachaud, David; Stewart, Michael; Royal Commission on the Distribution Income and Wealth (London : H.M.S.O., 1978)
This is a report that inquire into and report upon such matters concerning the distribution of personal incomes, both earned and unearned, and wealth as may be referred to it by the government.
Includes bibliographical footnotes: p. 188-190.
ahz 04/04/2019
Loans
Keywords: Poor